Anti-C1q antibodies: a biomarker for diagnosis and management of lupus nephritis. A narrative review - Calatroni, Marta; Moroni, Gabriella; Conte, Emanuele; Stella, Matteo; Reggiani, Francesco; Ponticelli, Claudio (Frontiers in Immunology, 2024)
Nephritis is a frequent and severe complication of Systemic Lupus Erythematous (SLE). The clinical course of lupus nephritis (LN) is usually characterized by alternating phases of remission and exacerbation. Flares of LN can lead to deterioration of kidney function, necessitating timely diagnosis and therapy. The presence of autoantibodies against C1q (anti-C1qAb) in the sera of SLE patients has been reported in various studies. Some research suggests that the presence and changes in the titer of anti-C1qAb may be associated with the development of LN, as well as with LN activity and renal flares. However, the exact role of anti-C1qAb in LN remains a subject of debate. Despite variability in the results of published studies, anti-C1qAb hold promise as noninvasive markers for assessing LN activity in SLE patients. Measuring anti-C1qAb levels could aid in diagnosing and managing LN during periods of both inactive disease and renal flares. Nevertheless, larger controlled trials with standardized laboratory assays are necessary to further establish the utility of anti-C1qAb in predicting the reactivation and remission of LN and guiding treatment strategies.